Effects of aquatic high intensity interval training on parameters of functional autonomy, mental health, and oxidative dysfunction in elderly subjects with type 2 diabetes - Doyenart, Ramiro; Boeira, Daniel; Milhomens, Yuri Pinheiro; Oliveira Silva da Silva, Vitória; Zilli Réus, Gislaine; Silveira, Paulo Cesar Lock; da Silva, Luciano Acordi (International journal of environmental health research, 2024)
The present study investigated the effects of aquatic exercise on parameters of functional autonomy, mental health, and oxidative dysfunction in elderly patients with DM2. A total of 130 elderly were included in the longitudinal clinical study and were attributed to the non-diabetic group (n = 27) and diabetes the group (n = 22). Both groups participated in 24 sessions of Hydro-HIIT, 48 h before and after Hydro-HIIT, the GDLAM index, depression, and anxiety scores and markers of oxidative dysfunction were quantified. After intervention, GI decreased in both groups (non-diabetes group = −24%; diabetes group = −22%) (p < 0.05), markers of depression (−46%), anxiety (−60%), DCFH-DA (−55%), SOD (+59%), TNF-α (−37%) and IL-1 (−48%) in diabetes group (p < 0.05). The intervention with Hydro-HIIT improves aspects related to functional autonomy, mental health, and exerts consequently, a modulating effect on oxidative stress and inflammatory response in elderly people diagnosed with DM2.